Unraveling the Relationship between Smoking and Weight: The Role of Sedentary Behavior. (27th September 2011) - Kaufman, Annette; Augustson, Erik M.; Patrick, Heather
Abstract : Research has shown that current smokers have a lower mean body mass index (BMI) than never and former smokers, with former smokers having the highest mean BMI. A number of physiological mechanisms have been hypothesized to explain this pattern, but few studies have explored the possible role of behavioral factors. Using data from the cross-sectional National Health and Nutrition Examination Survey 1999–2006, this descriptive study explored the associations among smoking status, sedentary behavior, and two anthropometric measures (BMI and waist circumference (WC)). Sedentary behavior was significantly higher among current smokers compared to never and former smokers; former smokers had higher levels of sedentary behavior compared to never smokers. The association between smoking status and anthropometric outcomes was moderated by sedentary behavior, with current smokers evidencing higher BMI and WC at higher levels of sedentary behavior compared to lower levels of sedentary behavior. Results are discussed in terms of their implications for interventions, particularly with respect to postcessation weight gain.